The Language Attitudes of Indonesian Language Teachers Toward the Acehnese Language - Pujiono, Mhd; Kiki Wardana, Muhammad; Taib, Rostina; ., Zuindra; Anayati, Wan (KnE Social Sciences, 2023)
Language attitudes are one area in sociolinguistics that needs to be explored. This research highlights the language attitudes of Indonesian language teachers and lecturers in Banda Aceh city toward their own mother tongue, the Acehnese language. This paper aimed to figure out the attitudes of teachers as native speakers of the Acehnese language and their language of preference in the educational context. The novelty of this research lies in the object of the research, that is, teachers, keeping in mind that recent publications about language attitudes have only revolved around students or parents. In executing the research, the researchers opted for qualitative methods to describe the phenomenon under study. The researchers used a descriptive approach to link, depict, and formulate the results and discussion. Questionnaires were used openly and closely to interview the respondents. The results of this research explained that Indonesian language teachers demonstrated strong, confident, affirmative, and flexible attitudes toward the Acehnese language. Keywords: sociolinguistics, language attitudes, language usage, Indonesian language teachers